Identifikasi Potensi Acid Rock Drainage Pada Tambang Timah di Pulau Bangka - Delita Ega Andini; Fajar Indah Puspita Sari (Jurusan Teknik Pertambangan, Fakultas Teknik, Universitas Bangka Belitung, 2020)
Bangka Belitung is one of the tin-producing areas in the world which is characterized by the large number of granite rocks in the area as the rock carrying cassiterite minerals. Granite rocks found on Bangka Island are rocks formed due to magma activity from acidic volcanic processes. The availability of acidic water is possible due to the presence of acid-carrying minerals from granite which causes acid rock drainage or acid rock water which generally occurs in mining areas, ex-mining and exploration in tin mines. Before making efforts to prevent environmental pollution, identification is needed regarding the potential acidity of the rock so that the pH and dissolved metal content that endangers survival can be prevented to a minimum.